(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In our country, the number of pregnant women with rhesus sensibility every year remains unchanged and does not have a downward trend. This is due to insufficient prophylaxis after the termination of pregnancy (spontaneous abortion, ectopic pregnancy, the birth of a rhesus-positive fetus) with the use of immunoglobulin against antiretroviruses. Previously effective methods of treatment, such as desensitization of antigens, plasmapheresis, hemosorption and intravenous administration of immunoglobulins, have only historical significance. Objective: to study and analyze the literature data of foreign and local authors on the diagnosis of hemolytic disease of the fetus, the use of non-invasive methods of Prevention of Rh-immunization. Search strategy: the search for information contained information such as regulatory documents, diagnostic protocols, and the conduct of RH-controversial pregnancy. Also in the databases Google Scholar, the Cochrane Library, PubMed, Library full-text scientific articles were used. Inclusion criteria: randomized, cohort study data, systematic reviews, diagnostic protocols, and Rh-conflict pregnancy. Exception criteria: practice, report, newspaper publications, articles describing theses. Results: studies have shown that the prophylactic purpose and administration of anti-D-immunoglobulin, which is used during 28-30 weeks of pregnancy, significantly reduces the development of immunization after childbirth. Conclusion: due to the wide application of anti-D-immunoglobulin in pregnant women and family planning, it will be possible to reduce the frequency of immunization, but the goal will be achieved only if a clear сomplex prevention of Rh-immunization is developed, in which the appearance of hemolytic disease of the fetus occurs. Nevertheless, the diagnosis and treatment of hemolytic disease remains an urgent problem and requires the use of new possibilities of modern medicine in the field of genetics, ultrasound diagnostics, invasive and non-invasive methods.